2019
DOI: 10.1177/1074295619836076
|View full text |Cite
|
Sign up to set email alerts
|

Proceed With Caution: Using Web-Based Resources for Instructing Students With and at Risk for EBD

Abstract: A new student, Aiden Rayburn, who is eligible for special education services with an emotional disorder, has joined Ms. Nelson's third-grade classroom. Ms. Nelson received information from his previous school that Aiden has a hard time sitting in his seat and frequently engages in behaviors like slamming his fists on the table when he is frustrated. Ms. Nelson wants to make sure that she is adequately prepared to meet his needs, so she begins to search for ideas on ways to help him stay on task and manage his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Generally, researchers and teams of experts who comment on the quality and effectiveness of online supplemental materials find them lacking. Researchers have warned that resources downloaded from the internet are no substitute for good pedagogy, especially for students with special needs (Beahm et al, 2019; Miller, 2015). A content analysis of Pinterest posts related to operations with negative integers found that 31% of pins contained conceptual errors and just 15% of pins provided any real-world context for the math exercises (Hertel & Wessman-Enzinger, 2017).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Generally, researchers and teams of experts who comment on the quality and effectiveness of online supplemental materials find them lacking. Researchers have warned that resources downloaded from the internet are no substitute for good pedagogy, especially for students with special needs (Beahm et al, 2019; Miller, 2015). A content analysis of Pinterest posts related to operations with negative integers found that 31% of pins contained conceptual errors and just 15% of pins provided any real-world context for the math exercises (Hertel & Wessman-Enzinger, 2017).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…For practitioners who receive training in single-case research methodology, such as board certified behavior analysts, the situation is still problematic, as these practitioners must continually wade through more research every year to identify a rigorous study without the expectation that recent publications will be more rigorous. Difficulty associated with locating rigorous research to support instructional decision making in applied educational settings may contribute to the frequent use of alternative sources, such as web-based resources, for decision-making for students in special education (e.g., Pinterest and Teachers Pay Teachers; Beahm et al, 2019;Cleaver & Wood, 2018). Given that there is a small likelihood that these web-based resources include research-supported practices (Beahm et al, 2019), future studies should investigate how practitioners differentiate high-and low-quality studies when selecting research to support instructional decision-making given the findings in this article.…”
Section: Practitioner Implicationsmentioning
confidence: 99%
“…Difficulty associated with locating rigorous research to support instructional decision making in applied educational settings may contribute to the frequent use of alternative sources, such as web-based resources, for decision-making for students in special education (e.g., Pinterest and Teachers Pay Teachers; Beahm et al, 2019;Cleaver & Wood, 2018). Given that there is a small likelihood that these web-based resources include research-supported practices (Beahm et al, 2019), future studies should investigate how practitioners differentiate high-and low-quality studies when selecting research to support instructional decision-making given the findings in this article. Graphs display the estimated trend lines indicating the probability of a study containing a design meeting What Works Clearinghouse (WWC) standards for rigor when studies contain (i.e., comparison group) and do not contain (i.e., treatment group) a multiple-probe design; top graph trend lines are calculated using average coefficient estimates from Model 3; bottom graph trend lines are calculated using the upper-bound 95% confidence interval estimate for ZXT variable and all other variables held constant from Model 3.…”
Section: Practitioner Implicationsmentioning
confidence: 99%
“…Despite mixed evidence supporting their utility, the provision of sensory materials in the environment continues to be a popular intervention selected by occupational therapists, teachers, and families to improve attention and engagement for students with autism (Beahm et al, 2019; Piller & Pfeiffer, 2016; Schecter et al, 2017). Common sensory materials’ interventions include handheld materials such as fidget toys (e.g., fidget spinners; Aspiranti & Hulac, 2022; Ledford et al, 2023) and alternative seating such as therapy balls (Bagatell et al, 2010) or therapy cushions (Umeda & Deitz, 2011).…”
mentioning
confidence: 99%